Peningkatan Kesejahteraan Masyarakat melalui Education and Traning of Eunterpreneurship Program Digital Marketplace Desa Cibadak - Jamaludin, Jamaludin; Husenudin, Abdul; Pamungkas, Jastin Dwi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research explores the potential of digital marketplaces in enhancing community welfare and evaluates entrepreneurship development strategies through the Education and Training of Entrepreneurship Program Digital Marketplace model at Desa Cibadak Kecamatan Ciampe Kabupaten Bogor. The main findings indicate that digital marketplaces expand market access, improve operational efficiency, promote financial inclusion, and create job opportunities. This digital entrepreneurship training program has proven effective in enhancing participants' knowledge and skills, as well as providing significant mentoring and support. Program impact evaluation shows increased participant income, local economic empowerment, and positive social impacts, including increased self-confidence and motivation. The conclusion of this research affirms that digital marketplaces and digital-based entrepreneurship training programs play a crucial role in supporting economic growth and community welfare, emphasizing the importance of sustainable strategies to provide significant benefits for individuals and communities.